Adsorption of Methylene Blue Using Activated Carbon Bioadsorbent Coffee Grounds and Reed Grass Without Flow Rate - Irwan Hidayatulloh; Dianty Rosirda Dewi Kurnia; Heni Anggorowati; Emma Hermawati Muhari; Luthfiana Kharisma; Radianti Novita Sari; Tifa Paramitha; Rony Pasonang Sihombing (Department of Chemical Engineering, Politeknik Negeri Bandung, 2024)
Methylene blue adsorption research has been conducted using bioadsorbents from activated carbon of coffee grounds and reeds. Coffee grounds and reeds contain carbon and cellulose that are effective for binding dyes. This study aims to determine the characteristics of activated carbon from coffee grounds and reeds based on SNI-06-3730-1995 and assess the color reduction of wastewater referring to the Decree of the Minister of Environment No. 51/MENLH/1995, which sets the maximum methylene blue content in industrial wastewater at 5-10 mg/L. The research method includes bioadsorbent preparation, characterization, and adsorption process with UV-Vis spectrophotometric analysis. Mass ratio variation was conducted on each adsorbent at each contact time variation and methylene blue concentration variation. The results of the analysis showed that the activated carbon of coffee grounds and reeds fulfills SNI-06-3730-1995 which is characterized by values that are below the maximum value in each parameter. The effectiveness of methylene blue adsorption by coffee grounds and reeds activated carbon reached 98.15% at a ratio of coffee grounds and reeds activated carbon 0:1 (w/w) for 120 minutes at a concentration of 25 mg/L. The adsorption capacity using the Freundlich isotherm method on reed activated carbon was 1.100 mg/g and coffee grounds activated carbon was 1.019 mg/g. The adsorption process of coffee grounds and reeds activated carbon has no effect on the carbon and cellulose structure of coffee grounds and reeds contained in activated carbon, namely O-H, C-H, C=C, and C=O.